2006
DOI: 10.1016/j.chemosphere.2005.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Oxalate and root exudates enhance the desorption of p,p′-DDT from soils

Abstract: The abiotic desorption of p,p 0 -DDT from seven Chinese soils spiked with p,p 0 -DDT and the effects of oxalate at 0.001-0.1 M and the root exudates of maize, wheat, and ryegrass were evaluated using batch experiments. Soil organic carbon played a predominant role in the retention of DDT. Oxalate significantly increased the desorption of p,p 0 -DDT, with the largest increments ranging from 11% to 54% for different soils. Oxalate addition also resulted in the increased release of dissolved organic carbon and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 26 publications
2
30
1
1
Order By: Relevance
“…n-Butanol has been used as an appropriate extraction solvent to determine the availability of organic contaminants in soils (Cui et al 2013;Liste and Alexander 2002;Kelsey et al 1997). Enhanced availability of some organic contaminants including PAHs and PCBs in soils by root exudates have been reported (White et al 2003(White et al , 2006Luo et al 2006), which were consistent with the observations of this study. After their addition to soils, root exudate components would be included in the soil DOC.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…n-Butanol has been used as an appropriate extraction solvent to determine the availability of organic contaminants in soils (Cui et al 2013;Liste and Alexander 2002;Kelsey et al 1997). Enhanced availability of some organic contaminants including PAHs and PCBs in soils by root exudates have been reported (White et al 2003(White et al , 2006Luo et al 2006), which were consistent with the observations of this study. After their addition to soils, root exudate components would be included in the soil DOC.…”
Section: Discussionsupporting
confidence: 88%
“…Biological activity, especially root exudation, has been demonstrated to significantly affect the behaviors of organic contaminants in soils (Luo et al 2006;Zhu et al 2009;Balseiro-Romero et al 2014;Martin et al 2014;He et al 2015). Some studies have evidenced the effects of root exudates on the desorption and availability of organic contaminants in soils.…”
Section: Introductionmentioning
confidence: 99%
“…Gonzalez et al (2010) showed that sodium citrate and oxalate, at levels usually exuded by plant roots, effectively enhanced desorption of p,p'-DDT, p,p'-DDE and α-cypermethrin, while no effects were observed for α-endosulfan and endosulfan sulfate, the non-ionic surfactant Tween 80 behaved similarly to the acids, whereas the anionic sodium dodecyl sulfate enhanced desorption of all pesticides (Gonzalez et al, 2010). Luo et al (2006) reported that soil organic carbon played a predominant role in the retention of DDT. Oxalate significantly increased the desorption of p,p'-DDT, with the largest increments ranging from 11% to 54% for different soils.…”
Section: Interaction Mechanism Between Lmwoa and Pesticides In Soilmentioning
confidence: 99%
“…Root exudates had similar effects to those of oxalate and significantly increased DDT desorption from the soils. So, Low molecular weight dissolved organic carbon amendments caused partial dissolution of the soil structure, such as the organo-mineral linkages, resulting in the release of organic carbon and metal ions and thus the subsequent enhanced desorption of DDT from the soils (Luo et al, 2006). We can put forward some mechanisms about the LMWOA or root exudates with OCPs desorption: (1) Mechanism of minerals dissolution.…”
Section: Interaction Mechanism Between Lmwoa and Pesticides In Soilmentioning
confidence: 99%
“…多 环 芳 烃 (polycyclic aromatic hydrocarbons, PAHs)是环境中普遍存在的持久性有机污染物, 多 数具有致癌、致畸或致突变效应 (Chen & Liao, 2006)。因其性质稳定、水溶性差, 易于被土壤颗粒 吸附, 土壤中PAHs含量逐年上升 (Tao et al, 2004;Li et al, 2006), 严重威胁着土壤环境质量及农产品 质量安全; 土壤中PAHs的迁移转化行为及其环境 效应已成为环境修复领域的研究热点 (Mueller & Shann, 2006;Lakshmanan et al, 2014)。 植物的存在能加快土壤中PAHs的去除 (Joner & Leyval, 2003;Kim et al, 2004;Gao et al, 2006), 根 系分泌物(root exudates)营造的根际微生态特征则 是影响PAHs快速消解的重要原因 (Sumia et al, 2013;Tejeda-Agredano et al, 2013)。植物修复过程中, 根 系分泌物在改善土壤属性、提高污染物的生物可利 用性、缓解环境胁迫等方面具有重要作用 (Bertin & Yang, 2003;Phillipsa et al, 2012;Shahzad et al, 2015)。一方面, 根系分泌的某些胞外酶能够直接参 与PAHs的降解过程; 另一方面, 分泌物中的可溶性 糖、低分子量有机酸、氨基酸等物质, 为根际微生 物提供充足的营养, 增加根际微生物的数量、提高 微生物活性 , 进而加速 PAHs 降解 (Susarla et al, 2012); PAHs的环数越多, 根际效益越明显 。不同植物间, 因根系分泌物的组成成分 及其释放特征常存在一定差异, 对根际微生物的区 系结构、 代谢活性的影响也不一样, 进而表现出不同 的修复潜力 (Kirk et al, 2005;Luo et al, 2006;Hunter et al, 2014) …”
unclassified